Prevalence and Regional Distribution of Beta-Hemoglobin Variants in Saudi Arabia: Insights from the National Premarital Screening Program" - Mansour Aljabry; Suha Sulimani; Ghazi Alotaibi; Hassan Aljabri; Shaker Alomary; Omar Aljabri; Maha Sallam; Abdulrahman Alsultan (Springer, 2024)
Abstract Background Hemoglobinopathies are among the most prevalent inherited disorders globally, with carrier prevalence varying significantly across regions. In Saudi Arabia, high rates of consanguineous marriages amplify the risk of these disorders. Aim This study aims to assess the burden of hemoglobinopathies by evaluating the prevalence and regional distribution of beta-hemoglobin variants, including rare variants, among couples participating in the national premarital screening program. Methods Data were collected from the premarital genetic screening program and entered into the SEHA platform, covering the 13 administrative regions of Saudi Arabia. Blood samples underwent various screening tests for infectious and genetic diseases. Hemoglobin electrophoresis samples were analyzed using capillary electrophoresis, High-Performance Liquid Chromatography (HPLC), or a combination of both methods. Results From 2011 to 2018, 1,871,184 individuals were included in the study, with 49.8% male and 50.2% female. The average age was 30.2 years. Hemoglobin S (HbS) was identified in 88,431 individuals (4.7% of the tested population and 78.5% of abnormal screening results), primarily as a sickle cell trait. β-thalassemia was the second most common disorder, identified in 22,420 individuals (1.2% of the population and 19.9% of hemoglobin disorders). HbC and HbD were each detected in 0.04% of cases, while HbO-Arab was identified in 0.007% and HbG in 0.006%. Hemoglobin E and hemoglobin Lepore were found to be extremely rare. Conclusion The study demonstrates regional variation in the prevalence of hemoglobin genetic variants in Saudi Arabia. To effectively mitigate this risk, it is imperative to strengthen public education and awareness, particularly focusing on genetic screening and counseling.